The The first record for the shore crab, Cyclograpsus aff. integer (Cyclograpsinae: Varunidae: Grapsoidea) from the Egyptian coasts of the Red Sea : Cyclograpsus integer - El-Sayed, Awaad; Abdalkhalek, Abudllah; Amer, Mohamed (Journal of King Abdulaziz University: Marine Sciences, 2025)
The shore crab, Cyclograpsus aff. integer (Subfamily Cyclograpsinae, Family Varunidae: Superfamily Grapsoidea), is recorded for the first time from the Egyptian Red Sea coasts and from the entire Red Sea. This species is a small-sized crab, lives in burrows at the upper intertidal zone of the sandy-mud and sandy bottom mixed with small pebbles. The diagnostic characters with illustrations distinguished it from other closely allied species were given. All information on crab habitat, color, diagnostic and morphological characters of this species were given and discussed.